Dairy protein–ligand interactions upon thermal processing and targeted delivery for the design of functional foods. (June 2019) - Condict, Lloyd; Paramita, Vilia Darma; Kasapis, Stefan
Graphical abstract: Highlights: Dairy protein matrix allows for controlled release of bioactive compounds. Coupling between bioactive compound and polymeric matrix determines diffusion. Dairy protein–phenolic interactions are heat treatment dependent. UHT induced protein–ligand interactions appear to be primarily chemical in nature. Abstract : Optimal protein performance in techno-functional and bio-functional foods is largely determined by thermal processing, leading to physical or chemical interactions with other constituents found in the commercial formulation. There is a need to understand at a fundamental level the kinetics of molecular transport of bioactive compounds, including vitamins, essential fatty acids, antioxidants and caffeine, from protein-based excipients in nutraceutical-type products. Physical interactions in these systems are further manipulated by crosslinking the protein network for controlled delivery in relation to the physicochemical environment of the release medium. Altering the processing conditions from ambient and pasteurisation temperatures to UHT treatment brings into play the denaturation of the milk protein, added to beverages that affects its association with phenolic compounds. These are found naturally in oat or wheat insoluble fibre, which is increasingly incorporated in formulations of added value foods, for example liquid breakfast. Potential formation of chemical interactions between hydroxycinnamic or hydroxybenzoic acids from insoluble dietary fibre and milk proteins following UHT processing and prolonged storage at ambient temperature may involve unexpected physiological and nutritional effects. We aim to review the significant results in this new and evolving field of dairy protein–ligand interactions in an effort to assist with planning further experiments for the design of convenient and nutritious foods.